2020
DOI: 10.1101/2020.02.24.962688
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IFN-λ4 is associated with increased risk and earlier occurrence of gastrointestinal, respiratory and malarial infections in Malian children

Abstract: Genetic polymorphisms within the IFNL3/IFNL4 genomic region encoding type III interferons have been strongly associated with impaired clearance of hepatitis C virus (HCV) infection. We hypothesized that this association might extend to the immune response to other pathogens as well. In a cohort of 914 Malian children enrolled at birth, we analyzed episodes of malaria, gastrointestinal and respiratory infections in relation to two genetic polymorphisms functionally affecting type III interferons -rs368234815 (I… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
4
5
0
Order By: Relevance
“…Genetic studies have shown that similar to its effect on HCV infections, the ΔG allele has a proviral effect in other respiratory viral infections and a similar risk phenotype in malaria infections. 25,26,27 The results shown here ascribe an overall Th2 phenotype to IFN-4, which may explain the above mentioned genetic association studies. We do note that our results from Figure 6B show an overall Th1 phenotype associated with IFN-4, whereas the results in Figure 9 show it to have a Th2 phenotype.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Genetic studies have shown that similar to its effect on HCV infections, the ΔG allele has a proviral effect in other respiratory viral infections and a similar risk phenotype in malaria infections. 25,26,27 The results shown here ascribe an overall Th2 phenotype to IFN-4, which may explain the above mentioned genetic association studies. We do note that our results from Figure 6B show an overall Th1 phenotype associated with IFN-4, whereas the results in Figure 9 show it to have a Th2 phenotype.…”
Section: Discussionsupporting
confidence: 75%
“…IFN-4 has been studied as an antiviral cytokine [1][2][3][4][5][6][7] ; however, the genetic association of the dinucleotide polymorphism rs368234815, which is responsible for IFN-4 expression, extends beyond viral infections, including several inflammatory disorders, [15][16][17][18][19][20][21][22] and even parasitic infections 27 and cancer. [28][29][30] Two SNPs are known to poten-tially regulate the expression of IFN-3 46,47 and it is not clear in many of the genetic associations which among IFN-3 and IFN-4 could be the causal factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…carriers of IFNL4-dG allele) negatively affects the ability to protect against P. falciparum malaria during infancy in children living in a malaria holoendemic region of East Africa. These results are consistent with a longitudinal study of children in Mali, West Africa [28]. The underlying mechanism as to why the ability to express a type III interferon is not protective against a parasitic infection remains an important question for future studies.…”
Section: Resultssupporting
confidence: 88%
“…The reason why the ancestral, IFNL4-dG allele, is still conserved in the African population and has not changed to the derived human-speci c allele, IFNL4-TT allele, remains unknown. Carriage of the IFNL4-dG allele is clearly not providing protection against HCV [4,[7][8][9], respiratory infections [11], gastrointestinal infections [28], human coronavirus, HCoV-229E or MERS-CoV [29], and now we have found similar results for P. falciparum malaria in children. Undoubtedly there are other selection pressures conserving this allele in this population.…”
Section: Discussionsupporting
confidence: 67%